A Review Of Antifungal Effect Of Plant Extract Vs Chemical Substances Against Malassezia Spp. - CHANDRANI, D.,; LUBAINA, S.Z,; SOOSAMMA, M, (International Journal of Pharma and Bio Sciences, 2012)
Flaking of the scalp is a symptom of seborrhoeic dermatitis, also called dandruff. It frequently occurs around the folds of the nose and eyebrows in addition to the scalp. The epidermal layers of the scalp are continually replaced and the cells are pushed outwards and they flake off giving white or grayish patches on the scalp, skin and clothes. Oily scalp, hormones or a fungus Malassezia seems to be the cause of dandruff. Dandruff can be treated with over the counter products, which are shampoos containing antifungal and antibacterial ingredients like zinc-pyrithione and selenium sulfide, salicylic acid etc. These can only slow down the flaking. Herbal extracts have proved to be good alternatives for the chemical preparations. A number of herbal shampoos and polyherbal hair oils have excellent results due to their synergistic, antifungal, anti-inflammatory and immunostimulatory action.